Graft-versus-Leukemia Effect Following Hematopoietic Stem Cell Transplantation for Leukemia - Dickinson, Anne M.; Norden, Jean; Li, Shuang; Hromadnikova, Ilona; Schmid, Christoph; Schmetzer, Helga; Jochem-Kolb, Hans (Frontiers in Immunology, 2017)
The success of haematopoietic stem cell transplantation (HSCT) lies with the ability of the engrafting immune system to remove residual leukaemia cells via a graft versus leukaemia effect, caused either spontaneously post HSCT or via donor lymphocyte infusion. Graft versus leukaemia effects can also be initiated by allogeneic mismatched NK cells, antigen specific T cells and activated dendritic cells of leukemic origin. The history and further application of this graft versus leukaemia effect and the main mechanisms will be discussed and reviewed in this chapter.